Organic matter in bottom sediments of the Northeast Pacific - Evgeny A Romankevich (PANGAEA, 1976)
The book is devoted to study of diagenetic changes of organic matter and mineral part of sediments and interstitial waters of the Pacific Ocean due to physical-chemical and microbiological processes. Microbiological studies deal with different groups of bacteria. Regularities of quantitative distribution and the role of microorganisms in geochemical processes are under consideration. Geochemical studies highlight redox processes of the early stages of sediment diagenesis, alterations of interstitial waters, regularities of variations in chemical composition of iron-manganese nodules.
Supplement to: Romankevich, EA (1976): Organic matter of bottom sediments to the east of Japan and its influence on redox processes. In: Volkov, I.I. (Ed.), Biogeochemistry of Diagenesis of Ocean Sediments; Nauka Publ. (Moscow): in Russian, 5-19